Time-specific placental growth factor (PlGF) across pregnancy and infant birth weight in women with preexisting diabetes. (2nd July 2016) - James-Todd, Tamarra; Cohen, Allison; Wenger, Julia; Brown, Florence
Abstract: Objective : Determine the independent association between time-specific placental growth factor (PIGF)—a marker of placental vasculature—and infant birth weight in offspring of mothers with preexisting type 1 and 2 diabetes. Methods : A total of 150 women were recruited from Joslin Diabetes Center's/Beth Israel Deaconess Medical Center's Diabetes in Pregnancy Program. PlGF was measured up to four times during pregnancy. Infant birth weight and covariate data were collected from medical records. Hemoglobin A1c was assessed from drawn blood samples. We used generalized linear and log-binomial models to calculate the change in continuous birth weight, as well as macrosomia for every unit change in time-specific ln-transformed PlGF, respectively. Models were adjusted for potential confounders. Results : Approximately 75% of women had type 1 diabetes. Third trimester PlGF levels were significantly associated with infant birth weight ( r = 0.24, p = 0.02 at 27–34 weeks; r = 0.26, p < 0.009 for 36–40 weeks). After full adjustment, there was a 6.1% and 6.6% increase in birth weight for gestational age percentile for each unit increase in ln-transformed PlGF level at 27–34 weeks and 35–40 weeks, respectively (95% CI for 27–34 weeks gestation: 1.1, 11.0, and 95% CI for 35–40 weeks gestation: 0.7%, 12.5%). We found a statistically significant increased risk of macrosomia among women with higher ln-transformed PlGF levels (RR: 1.72; 95% CI: 1.09, 2.70). Associations were not mediated by hemoglobin A1c. Conclusions : Third trimester PlGF levels were associated with higher birth weight in women with preexisting diabetes. These findings may provide insight to the pathophysiology of fetal overgrowth in women with diabetes.